A brief observation of morphological and behavioral similarities between the Ichneumonidae wasp Cryptanura sp. and its presumed mimic, Holymenia clavigera (Heteroptera: Coreidae), in Brazil - AIA Pereira; GS Andrade; JC Zanuncio; AM Penteado-Dias; JE Serrão (Brazilian Journal of Biology)
Some insects use wasps as a model to mimic and previous studies showed cases of Batesian mimicry involving this insect group. However, this relation is poorly known between phytophagous bugs, such as coreids, and Cryptinae ichneumonids. We found in a seasonal secondary forest in Brazil two similar insects representing different orders. The mimic seems to be Holymenia clavigera (Herbst) (Heteroptera: Coreidae) and its model, Cryptanura sp. (Hymenoptera: Ichneumonidae). This study therefore investigated similarities in morphological and behavioural aspects between H. clavigera and the wasp Cryptanura sp. Holymenia clavigera and its ichneumonid model are impressively similar in colour, size, foraging behaviour and sympatric range. The spanning movements of antennae by the coreid bug, which strongly resemble the foraging behaviour of the wasp, were observed frequently. The findings indicate strong evidences that H. clavigera is a mimic of the Ichneumonidae wasp, Cryptanura sp.